2006
DOI: 10.1136/sti.2005.017129
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine and sildenafil (Viagra) use are linked to unprotected receptive and insertive anal sex, respectively, in a sample of men who have sex with men

Abstract: Objectives: There is evidence that methamphetamine and sildenafil (Viagra) use are associated with sexual risk behaviour among men who have sex with men (MSM). We investigated the association of methamphetamine, sildenafil, and other substance use with unprotected receptive and insertive anal sex among MSM by conducting an encounter specific analysis. Methods: Data were from a cross sectional, community based survey of MSM in San Francisco regarding behaviour during their most recent anal sex encounter. Mulitv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 18 publications
10
115
2
2
Order By: Relevance
“…For example, crack cocaine has been associated with trading sex for drugs (Edlin et al, 1994;Marx et al, 1991), and among MSM, nitrites (Ostrow et al, 1990;Ostrow et al, 1993) and methamphetamine (Colfax et al, 2004;Mansergh et al, 2006) may serve as triggers for risky sex. Heroin may reduce sexual interest and ability, while methamphetamine and cocaine are associated with increased sex drive (Zule and Desmond, 1999;Rhodes and Quirk, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, crack cocaine has been associated with trading sex for drugs (Edlin et al, 1994;Marx et al, 1991), and among MSM, nitrites (Ostrow et al, 1990;Ostrow et al, 1993) and methamphetamine (Colfax et al, 2004;Mansergh et al, 2006) may serve as triggers for risky sex. Heroin may reduce sexual interest and ability, while methamphetamine and cocaine are associated with increased sex drive (Zule and Desmond, 1999;Rhodes and Quirk, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of female drug users, condom use at a recent sexual encounter was not significantly associated with use of alcohol, injection drugs, crack, or noninjection drugs before sex (Tortu et al, 2000), while a study of drug injectors suggested decreased condom use when both sexual partners were using crack with sex (Friedman et al, 1999). Event-level studies of MSM have found more unprotected receptive anal intercourse among men who used stimulants before sex (Colfax et al, 2004;Mansergh et al, 2006), as well as no effects for drugs other than alcohol (Vanable et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…27 Methamphetamine and Sildenafil use are linked to unprotected receptive and insertive anal sex, respectively, in a sample of gay men. 28 Sildenafil use appears to have become a stable fixture of the sexual culture of gay men and is associated with a general behavioral risk patter for transmission of HIV and other sexually transmitted diseases. 29 The concomitant use of Viagra, testosterone, and antidepressants among HIV-seropositive gay and bisexual men has been associated with unintended negative effects because of the additive risk of side effects.…”
Section: Pharmaceuticals For Erectile Dysfunctionmentioning
confidence: 99%
“…JOURNAL OF MEDICAL TOXICOLOGY I VOLUME 4, NUMBER 2 I JUNE 2008 methamphetamine induce short-term erectile dysfunction due to vasoconstriction, and self-treatment with sildenafil and similar drugs has been reported [11]. It may be that use of yohimbe as a sexual enhancer is popularly promoted among illicit stimulant users, and represents a potentially risky drug-supplement combination.…”
mentioning
confidence: 99%